Aid, Social Policy and Development. (November 2015) - Addison, Tony; Niño‐Zarazúa, Miguel; Tarp, Finn
Abstract: This paper discusses past and current social policy strategies in the international aid architecture as an introduction to the UNU‐WIDER Special Issue. Beginning in the 1990s, aid strategy and policy shifted to put a stronger emphasis on human development. This accelerated with the Millennium Development Goals (MDGs) and will continue under the Sustainable Development Goals (SDGs) which have even more ambitious targets. The paper also assesses some of the concerns associated with the 'Paris‐style' aid modalities, and discusses major challenges for the future global development agenda. Copyright © 2015 John Wiley & Sons, Ltd. © 2015 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.